Powder drink of Permesia americana Mill. Seed with adding Zingiber officinale Rosc. Var Rubrum and Stevia rebaudiana L. to enhance Cardiovascular health - Agustin, Arum Dwi; Purwasih, Ratih (Faculty of Pharmacy, Universitas Pancasila, 2024)
In today’s modern era many people consume unhealthy foods, which can lead to decreased immunity. One way to increase immunity is by consuming functional drinks from Avocado seeds and red ginger, which is contain flavonoid compounds. This study aims to determine antioxidant activity in functional drinks of avocado seeds by adding red ginger and stevia. The method used in this research is a quantitative analysis using the UV-Vis Spectrophotometer instrument at a wavelength of 418 nm for F1, F2 and F3 were brown, had a characteristic smell of spices, and had a distinctive taste. The pH test results were 6.243 ± 0.025, 6.167 ± 0.045, and 6.089 ± 0.005 respectively. The raw material and functional drinks positively contain flavonoids. Flavonoid content in F1, F2, and F3 were 12.214 ± 0.009428%, 12.419 ± 0.009428%, and 12.624 ± 0.009428% respectively. Antioxidant test results for functional drinks showed an IC50 value of F1 and F2 were 118.30 ± 1.57 ppm and 105.88 ± 1.11 ppm, which is categorized as moderate levels of antioxidants, and F3 was 88.09 ± 1.62 ppm, which is categorized as strong levels of antioxidants.